2023
DOI: 10.3390/ijms24044095
|View full text |Cite
|
Sign up to set email alerts
|

Space Omics and Tissue Response in Astronaut Skeletal Muscle after Short and Long Duration Missions

Abstract: The molecular mechanisms of skeletal muscle adaptation to spaceflight are as yet not fully investigated and well understood. The MUSCLE BIOPSY study analyzed pre and postflight deep calf muscle biopsies (m. soleus) obtained from five male International Space Station (ISS) astronauts. Moderate rates of myofiber atrophy were found in long-duration mission (LDM) astronauts (~180 days in space) performing routine inflight exercise as countermeasure (CM) compared to a short-duration mission (SDM) astronaut (11 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The European Space Agency (ESA) and the National Aeronautics and Space Administration (NASA) recently started to use Space omics technology in cells, animals and astronauts in spaceflight [86][87][88] . A number of clock genes with epigenetic modifications was reported through the fundamental Space omics research carried out by the NASA GeneLab project 87 .…”
Section: Discussionmentioning
confidence: 99%
“…The European Space Agency (ESA) and the National Aeronautics and Space Administration (NASA) recently started to use Space omics technology in cells, animals and astronauts in spaceflight [86][87][88] . A number of clock genes with epigenetic modifications was reported through the fundamental Space omics research carried out by the NASA GeneLab project 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown a decrease in plasma lumican concentrations after 10 days of bed rest [84], while the administration of lumican partially prevents the reduction in muscle mass and muscle fiber cross-sectional area observed in muscles after two weeks of unloading [41], highlighting its role in protecting skeletal muscles. Notably, a recent proteomics analysis of astronauts observed that lumican protein expression in the soleus muscle is elevated after 11 days of spaceflight [85]. However, further verification experiments are needed to confirm the correlation between the elevation of lumican in muscle tissue and its decline in plasma under disuse conditions.…”
Section: Other Myokinesmentioning
confidence: 99%
“…Thus, a detailed understanding of normal muscle function and its cellular regulation including the dynamics of the skeletal muscle proteome, as compared to muscle wasting, is important for diverse biological and biomedical disciplines. This includes crucial aspects of lifestyle biology, health science and clinical medicine, including sports and exercise physiology [39,40], electro-stimulation therapy, research into skeletal muscle plasticity [43,257], disuse-related muscular atrophy and the effects of re-innervation [41,258,259], space flight medicine [260,261], neuromuscular diseases [44,45], frailty-associated muscle aging and biogerontology [47,[262][263][264], forensic medicine [265,266] and the meat industry [267,268]. Important topics in muscle cell biology that are gaining steady interest are the regulation of skeletal muscle mass [269], myokine signaling [270] and muscle-bone-fat crosstalk [271].…”
Section: Basic and Applied Myologymentioning
confidence: 99%